The Impact of Financial Crisis on the Non-Life Insurance Market in Lithuania : Will the Market Growth Expectations be Met? - Lakstutiene, Ausrine; Norvaisiene, Rasa; Stankeviciene, Jurgita; Krusinskas, Rytis (Olsztyn Economic Journal, 2015)
The article analyzes the insurance market trends, which have been determined by the financial crisis, and reveals the development features and prospects of non-insurance market, which accounts for almost 70% of the total insurance market, in Lithuania. The obtained results showed that after the market shrank by a quarter in 2009, the insurance sector is recovering, and while the volume of issued insurance premiums increased in 2013, they still remain lower than during the pre-crisis period. 2010 is a distinctive year for the Lithuanian non-insurance market due to a track of unusual abundance of adverse events. Throughout the analyzed period the structure of the non-insurance market issued portfolios remained the same in Lithuania, and throughout the whole analyzed period non-insurance market is dominated by Mandatory Third Party Liability Insurance (MTPLI), Voluntary vehicle insurance (CASCO) and Property insurances, which, according to estimates and analysts’ forecasts, have growth potential.